Quando o território constrói sentido : um estudo sobre o processo de sensemaking em um empreendimento urbano planejado - Turcatti, Karoline (My University, 2025)
Sensemaking is an interpretative process through which people construct an understanding of situations, focusing on how meaning is produced through social interactions. Territory encompasses the deliberate appropriation of a geographic space and its concrete and symbolic dimensions. The main objective of this research is to understand how a territory capable of stimulating the construction of collective meaning can generate competitive advantages for the companies operating there. The guiding question was: how does the creation of meaning occur through interaction with the territory? The research adopted a qualitative, exploratory approach, developed through a single case study of the planned neighborhood Parque Una, located in the city of Pelotas (Rio Grande do Sul/Brazil). The construction of the empirical study was preceded by a systematic review of the literature, from which a conceptual framework was developed that revealed, in light of the theory, dimensions of sensemaking based on the territory. This framework guided the data collection stage, carried out through 23 semi-structured interviews with entrepreneurs, collaborators and users of the territory, complemented by direct observations and documentary analysis. The analysis allowed us to validate the dimensions proposed in the framework and understand how they manifest themselves in the territory. Among the most recurrent dimensions are identity, neighborhood, sense of place, sense of community, care and territorial value. The results demonstrated that the territory can be understood as a strategic asset for organizations, influencing the creation of collective meaning, the feeling of belonging and the construction of organizational identity, while enhancing the expansion of its symbolic, relational and operational limits. The research also provides insights for developing urban planning projects focused on sensemaking, promoting social interaction and encounters, emphasizing individual perceptions and the quality of relationships between people and places. [resumo fornecido pelo autor]
Sensemaking é um processo interpretativo por meio do qual as pessoas constroem entendimento sobre situações, focando sobretudo em como o sentido é produzido nas interações sociais. Território abrange tanto a apropriação deliberada de um espaço geográfico quanto suas dimensões concretas e simbólicas. Esta pesquisa tem como objetivo principal buscar compreender de que maneira um território capaz de estimular a construção de sentido coletivo pode gerar vantagens competitivas para as empresas nele inseridas. Partiu-se da seguinte questão norteadora: como ocorre a criação de sentido a partir da interação com o território? A pesquisa adotou uma abordagem qualitativa, de natureza exploratória, desenvolvida por meio de um estudo de caso único do bairro planejado Parque Una, localizado na cidade de Pelotas (Rio Grande do Sul/Brasil). A construção do estudo empírico foi precedida por uma revisão sistemática da literatura, a partir da qual foi desenvolvido um framework conceitual que revelou, à luz da teoria, dimensões do sensemaking baseado no território. Esse framework, orientou a etapa de coleta de dados, realizada por meio de 23 entrevistas semiestruturadas com empreendedores, colaboradores e usuários do território, complementadas por observações diretas e análise documental. A análise permitiu validar as dimensões propostas no framework e compreender como elas se manifestam no território. Entre as dimensões mais recorrentes destacam-se identidade, vizinhança, senso de lugar, senso de comunidade, cuidado e valor territorial. Os resultados demonstraram que o território pode ser compreendido como um ativo estratégico para as organizações, influenciando a criação de sentido coletivo, o sentimento de pertencimento e a construção da identidade organizacional, ao mesmo tempo em que potencializa a expansão de seus limites simbólicos, relacionais e operacionais. A pesquisa também oferece subsídios para o desenvolvimento de projetos urbanísticos voltados à construção de sentido, à promoção do convívio social, com foco na percepção dos indivíduos e na qualificação das relações entre pessoas e território.
Keywords: Administração; Planejamento urbano; Comportamento organizacional; Management; City planning; Organizational behavior